A general cell marker for clonal analysis of Drosophila development. - Lawrence, P.A. (Journal of Embryology and Experimental Morphology, 1981)
The mitochondrial enzyme, succinate dehydrogenase, can be localized by specific histochemical stains. A naturally occurring variant which gives heat-labile enzyme is used to map a gene responsible for succinate dehydrogenase. New alleles at the sdh locus are produced by mutagenesis and most of these are found to be homozygous lethal to flies. However, clones of cells which are homozygous for the new alleles can be produced by mitotic recombination, and are found to develop normally. If the chromosome arm bearing an sdh allele also carried brown, clones can be found in the eye. At the border of the clone the brown and sdh phenotype coincide showing that the sdh phenotype is expressed as a cell autonomous marker. Clones of sdh have been observed in the adult epidermis, the muscles, the gut, the heart and oenocytes where they display a clear phenotype. This new marker may be useful in studying the development of the internal organs of Drosophila.